Effect of olive oil pomace applications at different irrigation levels on soil quality - Pelin Alaboz; Ahmet Ali Işildar; Bilge Batmaz; Satı Çağlar (Soil Advances)
Nowadays, drought problems due to global warming and waste management for sustainable lands are very important issues. In this study, the effect of olive pomace applications, which is olive waste was investigated at different irrigation levels. This study, which basically aims to determine the effect of on soil quality, includes the application of 0(D0), 0.5(D0.5), 1(D1), 2(weight/weight) (D2) % levels and irrigation water at 50(I0.5), 75(I0.75) and 100 (I1)% of the field capacity to a medium-textured soil. In the study, the creation of comparison matrices for the examined features was carried out according to the F-AHP method within the scope of the fuzzy importance scale, and the linear combination technique, which is a parametric approach, was used to determine the quality index. It was determined that an approximately 37 % increase in the organic matter content of the soil in the D2. While the positive linear relationships between applications and some macronutrient elements were found to be significant, the changes determined in the Zn and Mn did not show linearity. It was observed that the soils fell into the ''high” class only when the soil quality index values, which were determined to show a statistically significant change between 0.730 and 0.775 for applications, were observed to be in the ''high'' quality class, while the effects of irrigation water application were found to be similar. I1 was evaluated as the most effective irrigation water, and D1 and D2 were evaluated as the most effective applications. It has been concluded that the application forms can affect the disintegration and decomposition process, and on the other hand, the use of plant yield and productivity parameters can make a significant contribution to determining the changes in the soil quality index.